2021
DOI: 10.1017/jfm.2020.1049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nanoscale nuclei on cavitation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Bulk nanobubbles (NBs) generally refer to suspended bubbles with a diameter of less than 1 μm, which have excellent prospects for applications in many fields, such as water management, nanoscale surface cleaning, ultrasound imaging, drug delivery, and acceleration of the growth of living organisms . NBs can also act as cavitation nuclei, whereby the discrepancy between experiment and theory for the tensile strength of water can be explained. , Unlike surface NBs adhering to solid substrates, bulk NBs proceed with Brownian motion, leading to difficulty in direct observation. Surface NBs can be directly observed with atom force microscopy and attribute their stabilization to the contact line pinning effect, which compels surface NBs to evolve with a constant footprint radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk nanobubbles (NBs) generally refer to suspended bubbles with a diameter of less than 1 μm, which have excellent prospects for applications in many fields, such as water management, nanoscale surface cleaning, ultrasound imaging, drug delivery, and acceleration of the growth of living organisms . NBs can also act as cavitation nuclei, whereby the discrepancy between experiment and theory for the tensile strength of water can be explained. , Unlike surface NBs adhering to solid substrates, bulk NBs proceed with Brownian motion, leading to difficulty in direct observation. Surface NBs can be directly observed with atom force microscopy and attribute their stabilization to the contact line pinning effect, which compels surface NBs to evolve with a constant footprint radius.…”
Section: Introductionmentioning
confidence: 99%
“…6 NBs can also act as cavitation nuclei, whereby the discrepancy between experiment and theory for the tensile strength of water can be explained. 7,8 Unlike surface NBs adhering to solid substrates, bulk NBs proceed with Brownian motion, 9 leading to difficulty in direct observation. Surface NBs can be directly observed with atom force microscopy 10 and attribute their stabilization to the contact line pinning effect, 11 which compels surface NBs to evolve with a constant footprint radius.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, molecular dynamics simulations were performed to study the stability and kinetics of tension-induced cavities. Theoretical considerations and simulations showed that, for a finite-sized sample, two parameters, stretching factor and the initial unstretched volume of the sample, play a crucial role. It is especially important to understand how large the stretching factor should be, since it is directly connected to the amount of tension.…”
Section: Introductionmentioning
confidence: 99%
“…
A possible explanation [13] might be nanoscale solid or 52 gaseous nuclei [14] that reduce the threshold of an oth-53 erwise pure liquid.
54Here, we report on a potentially novel source for cav-55 itation: droplets of a highly non-polar liquid, which is 56 hydrophobic and lipophobic, namely perfluorocarbons 57 (PFC). The atomically smooth surface does not offer 58 hydrophobic cracks for stabilization of pre-existing gas 59 pockets.
…”
mentioning
confidence: 96%
“…A possible explanation [13] might be nanoscale solid or 52 gaseous nuclei [14] that reduce the threshold of an oth-53 erwise pure liquid.…”
mentioning
confidence: 99%